The phenomenology of life phenomena – in a nursing context - Delmar, Charlotte (Nursing philosophy, 2006)
The purpose of this article is to describe and develop knowledge about life phenomena in a life-philosophical and nursing context. Knowledge about life phenomena is part of a care-ethical understanding with a focus on relations. Life phenomena are to be understood as a generalized label for the various phenomena which are given with human existence. The Danish life philosophical tradition with the perspective of life as experienced has something to say in relation to a further refinement of the phenomenology of life phenomena. The refinement will be described as an ethical and existential understanding of the phenomena of nursing. The first part of the article takes a philosophical approach to the phenomenology of life phenomena. It attempts to locate life phenomena in relation to, respectively, needs, senses, and feelings. In order to maintain an overview, the attempt is made to separate needs, senses, and feelings, although in real life these are closely interwoven. The article also describes philosophy and life phenomena in relation to nursing as an empirical field. In nursing there is a risk that life phenomena become invisible to those whose task is to help the ill person adjust to a new life situation. For the nurse, it will be a continuing task, never completed, to develop a sensory-based, situation-determined attention to the patient. And the nurse must be continually aware of whether mere ‘need-oriented’ nursing is controlling her professional actions as a nurse. Taking a point of departure in the nurse’s sensory, situationally determined attention, the last part of the article focuses on needs, senses, and feelings in connection with the nurse being able to direct her attention to the patient’s life phenomena.